The Effect of Ethnoscience-Based Science Environment Technology Society (SETS) Learning Model in Learning Physics and Biology - Gunaria Siagian; Tomi Apra Santosa; Festiyed Festiyed; Yerimadesi Yerimadesi (Universitas Lambung Mangkurat, 2023)
This study investigates the effect of the ethnoscience-based Science Environment Technology Society (SETS) learning model on learning Physics and Biology. This type of research involves systematic research, literature reviews, and meta-analyses. The data sources were taken from an analysis of 100 international journals published from 2018 to 2023. Tracing data sources through Google Scholar, Eric, ScienceDirect, and ProQuest. The process of selecting data sources must meet the inclusion criteria analyzed by the JSAP application. The inclusion criteria in this study are: 1) the journal must be published in 2018–2023; 2) SINTA and Scopus/WOS must index the journal; 3) The journal uses experimental or quasi-experimental research methods; and 4) it has an effect size that can be calculated. The data collection technique is direct observation through the journal database. The results showed that the average effect size (ES = 0.873) is a large criterion. These findings explain that the ethnoscience-based Science Environment Technology Society (SETS) model significantly affects science learning. Furthermore, this SETS learning model helps students learn physics and biology more actively and creatively. These results are very important in evaluating the implementation of the school learning system. Furthermore, this ethnoscience-based SETS model must be applied in learning biology and physics to stimulate students to think critically.